Pain in adults with cerebral palsy : A systematic review - Ryan, Jennifer M.; Burke, Jessica; Byrne, Rachel; Capellari, Emily; Harvey, Adrienne; O'Connell, Neil E.; Omichinski, Donna; Rodby-Bousquet, Elisabet ; 0000-0001-8373-1017; Peterson, Mark (Developmental Medicine and Child Neurology, 2025)
Aim: To describe the prevalence and incidence of pain, identify prognostic factors for pain, determine psychometric properties of tools to assess pain, and evaluate effectiveness of interventions for reducing pain among adults with cerebral palsy (CP). Method: Six databases were searched to identify studies published since 1990 in any language that met eligibility criteria defined for each objective. Titles, abstracts, and full texts were screened by two independent reviewers. Results: Sixty-three studies were identified; 47 reporting prevalence, 28 reporting prognostic factors, four reporting psychometric properties, five evaluating intervention effectiveness. Pain prevalence ranged from 24% to 89%. Prevalence was higher among adults with CP than in adults without it. Communication function, sex, and age were prognostic factors for pain prevalence. Numerical, verbal, and pictorial rating scales were valid for assessing pain intensity in adults with CP. Pharmacological and surgical interventions had no effect on pain. An active lifestyle and sports intervention reduced pain in adults with CP compared with usual care. Interpretation: Many adults with CP experience pain, although prevalence estimates vary considerably. The quality of evidence for prognostic factors and interventions is very low to low. There is a lack of evidence about effective pain management among adults with CP.